Pengaruh Pendapatan Usaha Koperasi Terhadap Sisa Hasil Usaha pada Koperasi Bina Artha Ventura Tasikmalaya - Sholiha Kurniavie; Usep Riyadi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
This study was conducted to determine the influence of cooperative business income to business revenue at Bina Artha Ventura Tasikmalaya Cooperation. The method used in this study is correlational and descriptive method. The population of this study is the totality of all that is possible, the results of counting or measurement, quantitative and qualitative data about the particular characteristics of several years of cooperative business income collection completely and obviously that want to learn its characteristics. The writer took some of the revenues that is cooperative business income and operating revenues from 2014 to 2018 as research sample. In collecting the data, the writer conducted observation, interviews and documentation on the research object. After the data is collected, then the data is analyzed using product moment correlation coefficient, f-test, the coefficient of determination and t-test with a level (α) 5%. From the results, it is obtained by the correlation coefficient (r) = 0,819 with interpretation of "high". The category of "high" here is caused by cooperative business income increased from 2014 to 2018 so as to increase as well business revenue obtained. The Influence between the two variables hypothesis test using the F test and t test which gained 11,6 thitung> ttabel 6,39 then H0 rejected and Ha accepted which means there is significant influence between variable X with variable Y so that the hypothesis of this research was proved. The level of influence cooperative business income to operating revenue is 97%. So it can be concluded that there is significant influence between cooperative business income and operating revenues at Bina Artha Ventura Tasikmalaya Cooperation.